Polymerization‐Induced Wrinkled Surfaces with Controlled Topography as Slippery Surfaces for Colorado Potato Beetles. Issue 12 (27th April 2020) - Bergmann, Johannes B.; Moatsou, Dafni; Surapaneni, Venkata A.; Thielen, Marc; Speck, Thomas; Wilts, Bodo D.; Steiner, Ullrich
Abstract: Controlling the interaction of insect populations with their host plants has recently received renewed attention in the light of pest control. One way to modify the interaction of insects with their host plants in a non‐chemical way is through influence of their de/attachment. Insect detachment has been observed for textured biological and structured artificial surfaces with morphologies ranging from nano‐ to micrometers (0.3–1.5 µm). Here, the formation of design surfaces is investigated through plasma‐induced polymerization of acrylates. This produces pronounced surface wrinkles that are tunable by the manufacturing process. For certain parameters, the wrinkles resemble those of the adaxial side of rubber tree ( Hevea brasiliensis ) leaves, a natural example of particularly low friction. Traction force measurements on the bio‐inspired surfaces show significantly impacted insect attachment compared to flat surfaces of silica and polymeric materials, opening a pathway to the controlled manufacture of bio‐inspired slippery surfaces for insects that could potentially find use in advanced materials such as wall coatings. Abstract : Wrinkled surfaces with surface topographies inspired by biological leaf structures are produced using plasma polymerization of polymer mixtures. This polymer‐based system not only realizes tunable topographies from the nano‐ to the micrometer range, but also provides slippery slopes for insects that champion biological reference structures with low adhesion.